Al(iii)-responsive "off–on" chemosensor based on rhodamine derivative and its application in cell imaging. Issue 54 (4th September 2018) - Yu, Chunwei; Jian, Li; Ji, Yuxiang; Zhang, Jun
Abstract : In this work, a new rhodamine chemosensor (P ) with excellent photochromic properties upon vis irradiation was designed and synthesized. Abstract : In this work, a new rhodamine chemosensor (P ) with excellent photochromic properties upon vis irradiation was designed and synthesized. The fabricated chemosensorP could detect Al 3+ via the opening of the spirolactam ring of the rhodamine unit with high selectivity and sensitivity. The spirolactam ring opening was confirmed by NMR and infrared spectroscopy. Upon binding with Al 3+, the generated 1 : 1P -Al 3+ complex, confirmed by Job's plot titrations and mass spectrometry analysis, could exhibit a remarkable fluorescence enhancement with a limit of detection (LOD) of 0.16 μM. Furthermore, the sensing ofP to Al 3+ in vivo was also studied quantitatively and qualitatively in detail, and the results showed that the coordination betweenP with Al 3+ was reversible in living cells.